SEMINAL PROTEINS PROFILE BY GRADIENT SDS-PAGE ELECTROPHORESIS IN NARI SUWARNA RAMS - KAIMAL, PRATHIBHA; TANDLE, M K; SELVARAJU, S (The Indian Journal of Animal Reproduction, 2022)
A study on seminal proteins profile using 6-16% gradient SDS-PAGE electrophoresis was conducted in NARISuwarna rams. The majority of seminal plasma proteins were observed to be less than 100 kDa. Among these 26kDa were abundant followed by 68 kDa and 23 kDa proteins. Identification of these proteins will be useful in relatingthe semen quality and fertility.
Keywords: NARI Suwarna; seminal proteins; SDS-PAGE; electrophoresis